Structural performance evaluation of UHPC/conventional concrete cast on new Y-shape FRP stay-in-place formwork for concrete bridge decks. (July 2022) - Pournasiri, Emad; Pham, Thong M.; Hao, Hong
Abstract: Over the past few years, there has been a rise in the use of Stay-In-Place (SIP) structural formworks made of fibre reinforced polymer (FRP). This study investigates the performance of decks made of FRP SIP structural formworks with an improved configuration using conventional and ultra-high performance concrete under static loadings. The proposed new composite deck consisted of a glass fibre reinforced polymer plate stiffened with Y-shape ribs for resisting tensile and shear stresses while reinforcements was placed on the compressive side of the deck. The new composite deck was compared with conventional reinforced concrete solid decks and a composite deck consisting of square hollow section (SHS) stiffeners. Results showed that the deck made of Y-shape stiffeners failed in punching shear, and the use of Y-shape stiffeners significantly enhanced the ultimate strength and shear capacity of the proposed deck. It was also concluded that the voids in the concrete deck with SHS stiffeners resulted in lightweight structures but had a negative influence on the ultimate strength of the deck cast on FRP SIP formwork. Increasing the concrete strength from 34 MPa to 140 MPa resulted in a 71% enhancement in the maximum load-carrying capacity but did not considerably influence their stiffness.